Effect of Indole Acetic Acid on Growth and Physiology of a Cyanobacterium Spirulina Platensis: The Role of Indole-3-acetic Acid in Promoting Growth and Physiology of Spirulina Platensis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Growth and developmental processes of cyanobacteria can be influenced by a variety of environmental factors including phytohormones. Present study investigated the role of Indole-3-acetic acid (IAA), one of key phytohormones, in promoting Spirulina growth and its photosynthetic pigments. The results showed that IAA supplementation resulted in immediate increase in growth just after 24 hours of inoculation which may be due to the fact that IAA causes fairly rapid increase in cell wall extensibility. Notably, there was significant increase in growth of Spirulina supplemented with IAA at 25-50 g ml–1 by 20th day (p value < 0.01). Optical microscopy showed that IAA supplementation resulted in rapid growth after 1st day of inoculum. On 20th day at 50 g ml–1 of IAA application, there was approximately 30 increase in chlorophyll a content, 17 increase in carotenoid content and 14 increase in phycocyanin content. The protein content measured serially from 0-20 day showed significant difference when supplemented with different IAA regimes (F-statistics 77.39 p value < 0.001). Based on results, it is concluded that IAA, in appropriate quantity, can be used as growth promoter to increase the quantity of Spirulina produced with increased amount of photosynthetic pigments like chlorophylls, carotenes and phycocyanin thus enhancing antioxidant potential of Spirulina.